2016
DOI: 10.1111/1755-0998.12603
|View full text |Cite
|
Sign up to set email alerts
|

tipdatingbeast: an r package to assist the implementation of phylogenetic tip‐dating tests using beast

Abstract: Molecular tip dating of phylogenetic trees is a growing discipline that uses DNA sequences sampled at different points in time to coestimate the timing of evolutionary events with rates of molecular evolution. In this context, beast, a program for Bayesian analysis of molecular sequences, is the most widely used phylogenetic tool. Here, we introduce tipdatingbeast, an r package built to assist the implementation of various phylogenetic tip-dating tests using beast. tipdatingbeast currently contains two main fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 20 publications
(24 reference statements)
1
76
0
Order By: Relevance
“…Sampling times of the sequences were used to calibrate the molecular clock. Date-randomization tests (DRTs) were performed in R 3.3.1 using the Tip Dating Beast package (Rieux & Khatchikian, 2016) to determine the temporal signal in data sets. A data set was considered to have an adequate spread in sampling time if its average rate did not fall within the 95% confidence intervals (CIs) generated from 20 replicates of randomized dates (Ramsden, Holmes, & Charleston, 2009;Duchêne, Duchêne, Holmes, & Ho, 2015).…”
Section: Population Historic Dynamicsmentioning
confidence: 99%
“…Sampling times of the sequences were used to calibrate the molecular clock. Date-randomization tests (DRTs) were performed in R 3.3.1 using the Tip Dating Beast package (Rieux & Khatchikian, 2016) to determine the temporal signal in data sets. A data set was considered to have an adequate spread in sampling time if its average rate did not fall within the 95% confidence intervals (CIs) generated from 20 replicates of randomized dates (Ramsden, Holmes, & Charleston, 2009;Duchêne, Duchêne, Holmes, & Ho, 2015).…”
Section: Population Historic Dynamicsmentioning
confidence: 99%
“…We 246 used a clustered permutation approach in BEAST [49,50] (available from 247 http://beast.bio.ed.ac.uk/), asking whether the correlation was stronger 248 than expected if sampling dates were randomly assigned among clusters 249 of sequences sampled on the same date [51]. Clustered permutation tip 250 date randomization [51,52] was performed in R using the TipDatingBeast 251 package for 5 replicates [53] and used for Bayesian evolutionary reconstruc-252 tion in BEAST assuming the uncorrelated, relaxed molecular clock [54] 253 and Bayesian skyline demographic models [50]. Markov chain Monte Carlo 254 sampling of parameters and tree topologies was performed for 500 million 255 generations or until effective sample sizes (ESS) reached values greater 256 than 200 (after burn-in of 10%).…”
Section: Bayesian Phyloanatomic Reconstruction 230mentioning
confidence: 99%
“…Analysis of time-dependent phylogenetic clus-387 tering of sequences revealed significant genetic distinction between the two 388 different time points (S1 Table), indicating viral population turnover and 389 sufficient evolution during the sampling time interval, despite initiation of 390 therapy. Date randomization tests [51][52][53] were also performed to determine 391 if greater evolutionary change was occurring over the 12-month period 392 than would be expected by random sampling of available dates, confirming 393 measurable evolution between sampling time points (S8 Fig). Temporal 394 reconstruction in P01 indicated that the median time of transmission for 395 each of the well-supported transitions occurred prior to administration 396 of cART, although extending well into the first year post-therapy in this 397 individual (S7 Fig). Despite potential sampling variation that can accom-398 pany the spatial sampling strategy described for these individuals, temporal 399 inferences of the well-supported dispersion patterns in P01 overlapped by 400 as much as 100% among the three replicates of sequence sub-sampling (S7 401 Fig), indicating the robustness of the molecular clock analysis and BSSVS 402 approach.…”
mentioning
confidence: 95%
See 2 more Smart Citations